The Relationship of African Apes, Man, and Old World Monkeys - Leakey, L. S. B. (1970)
The conclusions of Wilson and Sarich (Proc. Nat. Acad. Sci. USA, 63, 1088-1093 (1969) that the human lineage diverged from that leading to the African apes about 4 to 5 million years ago is shown to be based upon a wholly unsupported assumption that the Superfamilies Hominoidea and Cercopithecoidea only separated from each other some 30 million years ago. This is entirely contrary to most recent palaeontological evidence.